Cpp1 phosphatase mediated signaling crosstalk between Hog1 and Cek1 mitogen-activated protein kinases is involved in the phenotypic transition in Candida albicans. (20th April 2017) - Deng, Fu-Sheng; Lin, Ching-Hsuan
Abstract: Cellular signaling pathways involved in cell growth and differentiation mediated by mitogen-activated protein kinase (MAPK) cascades have been well characterized in fungi. However, the mechanisms of signaling crosstalk between MAPKs to ensure signaling specificity are largely unknown. Previous work showed that activation of the Candida albicans Cek1 MAPK pathway resulted in opaque cell formation and filamentation, which mirrored the phenotypes to hog1Δ . Additionally, deleting the HOG1 gene stimulated Cek1p. Thus, we hypothesized that an unknown factor could act as a bridge between these two MAPKs. In Saccharomyces cerevisiae, the dual-specificity phosphatase (DSP) Msg5 specifically dephosphorylates Fus3p/Kss1p. C. albicans Cpp1, an ortholog of Msg5, has been shown to be important in regulating Cek1p. Compared with the wild-type strain, hog1Δ shows a ∼40% reduction in CPP1 expression. Consistent with previous reports, CPP1 deletion also resulted in Cek1 hyperphosphorylation, implicating Cpp1 as a regulator of the Hog1 and Cek1 cascades. Interestingly, both cpp1Δ and hog1Δ induced 100% opaque colony formation in MTL- homozygous strains grown on N -acetylglucosamine (NAG) plates, whereas the wild-type and complemented strains exhibited 80.9% and 77.1% white-to-opaque switching rates, respectively. CPP1 gene deletion also caused hyperfilamentous phenotypes in both white and opaque cells. These phenomena may be due to highly phosphorylated Cek1p, as deleting CEK1 in the cpp1Δ background generated nonfilamentous strains and reduced opaque colony formation. Taken together, we conclude that cpp1Δ and hog1Δ exhibited comparable phenotypes, and both are involved in regulating Cek1 phosphorylation, implicating Cpp1 phosphatase as a key intermediary between the Hog1 and Cek1 signal transduction pathways.